The Concept of Restorative Justice in the Framework of Customary Law in Indonesia - Syarif, Kurnia Ali (Program Pascasarjana Universitas Negeri Makassar, 2025)
This research seeks to examine the application of the restorative justice ideology in customary law in Indonesia and the obstacles it encounters in merging with the national legal framework. Restorative justice within Indonesian customary law emphasizes mending relationships among offenders, victims, and the community via community-oriented methods like customary discussions and social ceremonies. The study employs a legal-formative method to analyze pertinent legal rules and customary law practices that endorse the restorative justice model. The results suggest that applying restorative justice in traditional communities could speed up conflict resolution and lessen the pressure on formal legal systems. Nevertheless, the research also uncovers challenges, including the variance of regulations among various customary communities and scarce formal acknowledgment in the national legal framework. Through enhanced regulations and clearer guidelines, restorative justice is anticipated to be implemented more uniformly and aligned with human rights standards, thus fostering a justice system that prioritizes social restoration and inclusivity.